Evaluation of Proline Accumulation and Delta(1)-pyrroline-5-carboxylate Synthetase (P5CS) Gene Expression during Salinity Stress in Two Soybean (Glycine max L. Merr.) Varieties - ATAK, ÇİMEN; ÇELİK, ÖZGE (Hard, Post-Office Box, 10-718 Olsztyn 5, Poland, 2012)
The aim of our study was to compare the effects of salt stress in two soybean (Glycine max L. Merr) varieties. Two soybean genotypes (Ataem-7 and Ustun-1) were grown under 0, 50, 100, and 150 mM NaCl treatments, and the leaves were harvested for lipid peroxidation analyses, proline content and P5CS gene expression levels. According to the results of lipid peroxidation analysis, Ataem-7 variety was found to be more sensitive than Ustun-1 variety for NaCl stress. Proline is an important osmolyte accumulated under environmental stresses. As a response to salinity, we determined their proline levels. Proline accumulation in Ataem-7 variety increased 1:39 fold in accordance with Ustun-1 variety at 150 mM NaCl treatment. Glycine max Delta(1)-pyrroline-5-carboxylate synthetase (GmP5CS) gene expression levels under 50, 100 and 150 mM NaCl stress were determined. When the GmP5CS gene expression level was gradually increased in Ustun-1 variety, the highest gene expression level for Ataem-7 was determined at 100 mM NaCl. The GmP5CS gene expression in Ustun-1 at 150 mM NaCl increased 2.93 fold compared with 100 mM treatment. When we evaluate the relation between proline accumulation and expression levels of GmP5CS gene, it is obvious that accumulations of proline in two soybean varieties are under control of different mechanisms in the presence of salinity.
Keywords: salt stress; proline accumulation; soybean Delta(1)-pyrroline-5-carboxylate synthetase (GmP5CS); RT-PCR; high-yielding genotypes; lipid-peroxidation; antioxidative enzymes; tolerance; metabolism; cultivars; plants; nacl; increases; tuz stresi; prolin birikimi; yüksek verimli genotipler; antioksidan enzimler; hata payı; metabolizma; çeşitler; bitkiler; artışlar